EFFICACY OF USE OF TNF INHIBITOR ADALIMUMAB IN A FEMALE PATIENT WITH CHRONIC UVEITIS IN THE ONSET OF JUVENILE IDIOPATHIC ARTHRITIS - T. V. Pavkhun; I. K. Shishkina; I. V. Pishchyulina; M. K. Yusupova; L. V. Gorshkova (Педиатрическая фармакология)
The article presents a clinical case of successful use of adalimumab (monoclonal antibodies to TNF ) as a drug of choice for treating continuously recurrent chronic bilateral uveitis complicated with a cataract that developed in the onset of juvenile idiopathic arthritis long before articular syndrome in the absence of humoral activity in a child who developed the disease at the age of 12 years. Adalimumab therapy launch induced uveitis remission 12 weeks after initiation.